Radiofrequency Catheter Ablation of AVNRT - Rizzo, Toni (MD Conference Express, 2012)
This article discusses practical strategies for radiofrequency (RF) catheter ablation of atrioventricular nodal reentry tachycardia (AVNRT), including slow and fast pathway ablation. Furthermore, cryoablation versus RF for AVNRT is also discussed.